2006
DOI: 10.1111/j.1742-1241.2006.00829.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of superinfection following imipenem/cilastatin therapy in hospitalised patients with acute exacerbations of severe chronic obstructive pulmonary disease

Abstract: Imipenem is often used in treatment of acute exacerbations of severe chronic obstructive pulmonary disease (COPD). Superinfection following imipenem therapy is a common cause of treatment failure and high economic burden. This study is aimed to explore any clinical factors which determine the risk of superinfection after imipenem treatment in acute exacerbations of severe COPD. A prospective observational study was conducted in a 5-bed respiratory intensive care unit of a Chinese University hospital. Fifty-one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Superinfections caused by S. maltophilia, P. aeruginosa, and K. pneumoniae following the use of imipenem to treat patients with severe pneumonia have been reported (112). The treatment of patients with acute exacerbations of severe COPD with imipenem has been associated with a high (30.8%) risk of superinfection, including those caused by S. maltophilia and P. aeruginosa (91). The identification of imipenem as a risk factor for S. maltophilia infection has not been reported for all studies of S. maltophilia infections.…”
Section: Emergence Of Antibiotic Resistancementioning
confidence: 99%
“…Superinfections caused by S. maltophilia, P. aeruginosa, and K. pneumoniae following the use of imipenem to treat patients with severe pneumonia have been reported (112). The treatment of patients with acute exacerbations of severe COPD with imipenem has been associated with a high (30.8%) risk of superinfection, including those caused by S. maltophilia and P. aeruginosa (91). The identification of imipenem as a risk factor for S. maltophilia infection has not been reported for all studies of S. maltophilia infections.…”
Section: Emergence Of Antibiotic Resistancementioning
confidence: 99%
“…Risk factors for S. maltophilia sputum detection in the current study were similar to those found in cancer patients, immunocompromised hosts and individuals previously exposed to wide-spectrum antibiotics. 2 , 9 , 10 In addition, we found an association between S. maltophilia and COPD exacerbation, use of oral steroids and carbapenems which might represent targets for further preventive strategies.…”
Section: Discussionmentioning
confidence: 72%